The genus Leucophenga (Diptera, Drosophilidae), part VII: the subpollinosa species group from China, with morphological and molecular evidence - Huang, Jia; Su, Yirui; Chen, Hongwei (Zootaxa, 2017)
Seventeen species of Leucophenga subpollinosa species group are described from China (including 11 new species): L. argentina (de Meijere, 1924); L. flavicosta Duda, 1926; L. formosa Okada, 1987; L. nigroscutellata Duda, 1924; L. subpollinosa (de Meijere, 1914); L. umbratula Duda, 1924; L. aculeata sp. nov.; L. acuticauda sp. nov.; L. cultella sp. nov.; L. cyclophylla sp. nov.; L. flaviclypeata sp. nov.; L. fuscipedes sp. nov.; L. gracilenta sp. nov.; L. latipenis sp. nov.; L. magnicauda sp. nov.; L. rhombura sp. nov.; L. rugatifolia sp. nov. A key to all examined species of the subpollinosa group in the present study is provided. The phylogenetic relationships among the 17 species of the subpollinosa group are reconstructed by NJ (Neighbor-joining) and Bayesian analyses using 98 DNA sequences of COI (cytochrome c oxidase subunit I) gene. The pairwise intra- and interspecific p-distances of aforementioned sequences are summarized.